2016
DOI: 10.1007/s10897-016-9936-y
|View full text |Cite
|
Sign up to set email alerts
|

Put Yourself at the Helm: Charting New Territory, Correcting Course, and Weathering the Storm of Career Trajectories

Abstract: What bearing have you set you set your sights on? How do you navigate the ever-changing swells and winds of our professional landscape? Are you feeling a nebulous desire for change, that your career is not going in the direction you were expecting, worry about lack of future opportunities, or even a deep dissatisfaction in your current position? You are not alone. The formation of the Committee on Advanced Training for Certified Genetic Counselors (CATCGC) was partly in response to such sentiments, expressed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Using the constructivist framework described in Hippman & Davis (), we disclosed our committee composition in the introduction and provide further characterization of our perspectives here. Many committee members are employed in GC training and in research.…”
Section: Discussionmentioning
confidence: 99%
“…Using the constructivist framework described in Hippman & Davis (), we disclosed our committee composition in the introduction and provide further characterization of our perspectives here. Many committee members are employed in GC training and in research.…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of the profession, opportunities for career advancement were limited. With the development of the profession, opportunities abound and individual practitioners have personal responsibility to select activities and make choices that contribute to their own professional development (Hippman, Davis, & Committee on Advanced Training for Certified Genetic Counselors, ). These might include advocating for protected time and funding for professional development activities; self‐advocacy for deserved promotions; volunteering on a local, regional, or national basis; and accepting the risks associated with changing positions, embarking on an educational path (e.g., Redlinger‐Grosse, ), or accepting a promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our study identified that perceptions of being viewed negatively by their public practitioner peers were a significant challenge faced by genetic counsellors working in private practice, increasing feelings of isolation from the genetic counselling community. Perceptions of feeling negatively perceived have also been experienced by others in the genetic counselling profession in diversified positions, such as laboratory or research based positions (Groepper et al 2015;Zetzsche et al 2014;Hippman and Davis 2016). Negative perceptions can arise from preconceived ideas, misunderstandings, and lack of trust (Groepper et al 2015).…”
Section: Discussionmentioning
confidence: 99%